Oral health and quality of life: findings from the Survey of Health, Ageing and Retirement in Europe - Celina Block; Hans-Helmut König; André Hajek (BMC, 2022)
Abstract Background The aim of this study was to clarify the link between oral health and quality of life among older adults in Europe. Methods Cross-sectional data from wave 5 (n = 59,048 observations) were used from the representative Survey of Health, Ageing and Retirement in Europe. Oral health was quantified by three questions: presence of all natural teeth (yes; no); among individuals with missing natural teeth, the number of missing teeth and the extent of replaced natural teeth were quantified. Quality of life was quantified using the widely used CASP-12. Multiple linear regressions were used to determine the association between oral health and quality of life, adjusting for various potential confounders. Results Multiple linear regressions showed that higher quality of life was associated with (1) the presence of all natural teeth and among individuals with missing natural teeth, with (2) a lower number of missing natural teeth and (3) completely replaced natural teeth. Additionally, quality of life was positively associated with younger age, being female, being married or in a partnership, higher income, higher educational level, not currently smoking, a lower number of functional impairments, better self-rated health, a lower number of depressive symptoms and a lower number of chronic diseases. Conclusion Study findings showed an association between oral health and quality of life among older adults in Europe. Thus, the importance of good oral health for successful ageing was stressed. Future research is required to clarify the underlying mechanisms. Moreover, longitudinal studies are required to confirm our current findings.